A study on the relationship between exchange rate and stock price in China - DING, LIJIN (2017)
This dissertation investigates the relationship between exchange rate of Renminbi against U.S. dollars and five main index prices in the Chinese market. Shanghai Stock Exchange index (SSE), and four China Security Indices (CSI100, CSI200, CSI300 and CSI500) are selected as the sample series. Daily data ranging from 1st June 2010 to 10th August 2017 are used to study the relation between exchange rate and stock price. In empirical process, the ADF test proves that all variables are non-stationary but integrated of first order. Then I analyze the long-term relationship between index price and exchange rate through Johansen cointegration test and the results show no stable relationship between them except for CSI500 and exchange rate. Next, vector error correction model has been adopted to analyze the short-term interaction between CSI500 and exchange rate. For those Non-cointegrated pairs, Granger causality test has been performed to investigate the casual direction between variables. Finally, I used impulse function and variance decomposition to investigate dynamic behavior of these variables. The results of Granger causality test imply bidirectional causality between index price and exchange rate. And the impulse response function indicates that increasing index price return has positive shock effect on the differenced exchange rate during the sample period, while the increasing differenced exchange rate has negative shock effect on the stock return at first, and then the shock effect turns into positive and finally diminishes. The results of variance decompositions indicate that the impact from change in exchange rate to the index price is more obvious than the impact from change in index price to the exchange rate, which is consistent with the findings from Granger causality test.